2001
DOI: 10.1088/0264-9381/18/4/302
|View full text |Cite
|
Sign up to set email alerts
|

A quintessence scalar field in Brans-Dicke theory

Abstract: It is shown that a minimally coupled scalar field in Brans-Dicke theory yields a non-decelerated expansion for the present universe for open, flat and closed Friedmann-Robertson-Walker models.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
81
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 121 publications
(83 citation statements)
references
References 14 publications
1
81
1
Order By: Relevance
“…So, the idea of varying ω is crucial here as it can very well serve the purpose of providing a signature flip in q in this interacting scenario. It deserves mention that the specific choice for the interaction in equation (8) and the choice of ω = ω(φ) in equation (12) are taken so as to yield the desired result. This is indeed a toy model which simply shows that investigations regarding an interaction amongst matter and the nonminimally coupled scalar field is worthwhile.…”
Section: Discussionmentioning
confidence: 99%
“…So, the idea of varying ω is crucial here as it can very well serve the purpose of providing a signature flip in q in this interacting scenario. It deserves mention that the specific choice for the interaction in equation (8) and the choice of ω = ω(φ) in equation (12) are taken so as to yield the desired result. This is indeed a toy model which simply shows that investigations regarding an interaction amongst matter and the nonminimally coupled scalar field is worthwhile.…”
Section: Discussionmentioning
confidence: 99%
“…First of all, the holographic idea we have adopted to justify the EddingtonWeinberg relation is still just a conjecture, despite the several theoretical developments this subject has received in the last years [20]. On the other hand, the Friedmann equation (1) applied to this varying G context is something to be theoretically validated, for example in the realm of scalar-tensor theories [3,29]. It is possible to verify that our solutions, together with equation (1), are solutions of Brans-Dicke theories, and an exhaustive study about this will be shown elsewhere.…”
Section: Discussionmentioning
confidence: 99%
“…But why has m the order of the pion mass? The common belief is that a natural cutoff for the vacuum fluctuations should be given by the Planck mass m p = l (29) to (28) with m = m p , one obtains a Hubble radius of the order of l p , which is not consistent with our universe.…”
Section: Holography and G Variationmentioning
confidence: 98%
“…Thus the BD theory or its modified versions have been shown to account for the present acceleration of universe [13,14]. An observation regarding the BD theory is that it can potentially generate sufficient acceleration in the matter dominated era even without taking into consideration an exotic quintessence field [15]. However, the researchers have been looking for a theory which can explain the change of cosmic expansion state from deceleration to acceleration.…”
Section: Introductionmentioning
confidence: 99%